ANALISIS PENGARUH PENDAPATAN ASLI DAERAH TERHADAP KINERJA KEUANGAN PROVINSI SULAWESI SELATAN DI BADAN PUSAT STATISTIK SULAWESI SELATAN - Anwar Anwar (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
This study aims to analyze the effect of Regional Original Revenue on the Financial Performance of South Sulawesi Province at the Central Statistics Agency of South Sulawesi. The sample in this study is the Realization and Expenditure Realization Report for 21 Regencies and 3 Cities in South Sulawesi Province. The amount of data observed was 48 observational data. In this study using secondary data obtained from the Realization and Expense Realization Report of 21 Regencies and 3 Cities in South Sulawesi Province. The number of reports used is two years, namely 2013 and 2014. The analytical method used in this study is a simple linear regression analysis.The results showed the number of Original Revenue of Regencies / Cities in South Sulawesi in 2013-2014 there was an increase and decrease based on their respective regions. While the government's financial performance in all districts / cities experienced an increase. The impact of PAD on financial performance shows a significant positive effect.